Labor Market Frictions and Moving Costs of the Employed and Unemployed - Tyler Ransom (Institute of Labor Economics (IZA), 2019)
This paper examines the role of labor market frictions and moving costs in explaining the migration behavior of US workers by employment status. Using data on low-skilled workers from the Survey of Income and Program Participation (SIPP), I estimate a dynamic model of individual labor supply and migration decisions. The model incorporates a reduced-form search model and allows for migration for non-market reasons. My estimates show that moving costs are substantial and that labor market frictions primarily inhibit migration of the employed. I use the model to study migration responses to local labor market shocks and to a moving subsidy. Workers' preferences for non-market amenities, coupled with substantial moving costs and employment frictions, grant market power to incumbent employers. Large moving costs also likely affect employers' recruiting behavior.
Keywords: C35; E32; J22; J61; J64; R23; 330; migration; job search; dynamic discrete choice